2012
DOI: 10.1270/jsbbs.62.328
|View full text |Cite
|
Sign up to set email alerts
|

Persistent C genome chromosome regions identified by SSR analysis in backcross progenies between <i>Brassica juncea</i> and <i>B. napus</i>

Abstract: Given that feral transgenic canola (Brassica napus) from spilled seeds has been found outside of farmer’s fields and that B. juncea is distributed worldwide, it is possible that introgression to B. juncea from B. napus has occurred. To investigate such introgression, we characterized the persistence of B. napus C genome chromosome (C-chromosome) regions in backcross progenies by B. napus C-chromosome specific simple sequence repeat (SSR) markers. We produced backcross progenies from B. juncea and F1 hybrid of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…On the other hand, Di et al (2009) reported that F 1 hybrids from wild B. juncea × GM canola showed higher fertility than that reported previously (Bing et al 1991, 1996, Frello et al 1995, Tsuda et al 2012b). Di et al (2009) also reported that the vigorous vegetative and reproductive growth of wild B. juncea resulted in higher fertility rates of the F 1 hybrids.…”
Section: Conclusion and Remarksmentioning
confidence: 88%
See 1 more Smart Citation
“…On the other hand, Di et al (2009) reported that F 1 hybrids from wild B. juncea × GM canola showed higher fertility than that reported previously (Bing et al 1991, 1996, Frello et al 1995, Tsuda et al 2012b). Di et al (2009) also reported that the vigorous vegetative and reproductive growth of wild B. juncea resulted in higher fertility rates of the F 1 hybrids.…”
Section: Conclusion and Remarksmentioning
confidence: 88%
“…Most of the hybrids had chromosomes and an AABC genome composition (Choudhary and Joshi 1999, Tsuda et al 2012b). Pollen fertility of F 1 ranged from 0 to 35.6% (Choudhary and Joshi 1999, Frello et al 1995, Heenan et al 2007, Liu et al 2010, Sandhu and Gupta 2000, Song and Qiang 2003), with the highest fertility (78%) observed in nine samples of the F 1 hybrid.…”
Section: Introgression From B Napus To B Junceamentioning
confidence: 99%
“…The probability of stable introgression events depended on the survival and population growth of hybrid and backcross generations (Pallett et al ). There have been several studies demonstrating the transfer of either Bt (Frello et al , Halfhill et al , Zhu et al , Liu et al , Yang et al ) or herbicide‐resistance transgenes (Guéritaine et al , Tsuda et al ) to backcross generations. However, a low level of transgene introgression from transgenic herbicide‐resistant B. napus to different B. juncea varieties was estimated by artificial pollination (Tang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…SSR locus 83b1, which used a pair of C‐genome‐specific SSR primers (Szewc‐McFadden et al ), was also employed, although it was unknown on which C‐chromosome it was located. PCR reactions were performed according to Lowe et al () and Tsuda et al (). The annealing temperatures of all primer pairs are listed in Table 2.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation